Critical Review on New Indonesia Law on Labour Rights - Memed Hermanto; Sri Budi Purwaningsih (Indonesian Journal of Law and Economics Review, 2021)
After the promulgation of Law Number 11 of 2020 concerning Job Creation on November 2, 2020, many academics and practitioners considered material and formal defects who studied this issue. 2003 concerning Employment. So that the problems that arise related to the legal protection of workers' rights according to the Employment Copyright Act of labor clusters in the perspective of the East Java FSPMI, this is very far from the meaning of legal protection for workers. The purpose of this study is to examine the basic reasons for trade unions/labor unions in rejecting Law Number 11 of 2020 concerning Job Creation (employment clusters). The method used in this research is socio-legal which examines the perception and behavior of humans and legal entities that occur in the field, which emphasizes the importance of empirical observation, observation and analytical steps. The conclusion of this research is that when the Employment Copyright Law is enacted, there are still many shortcomings and weaknesses that tend to be detrimental to Workers/Labourers which of course has the potential to create new problems in industrial relations between employers and workers. Taking into account these conditions, it is clear that the position of workers/labourers does not have legal protection and there is a guarantee of justice in terms of protection of job security, protection of income certainty and protection of social security, this is far from the ideals of the spirit of labor law to provide protection for all workers and their families.